Effect of ZnO/B₂O₃ and ZnO/SiO₂ ratio on physical, structural and optical properties of willemite-based glass ceramic from waste rice husk - Khirel Azman, Aisyah Zakiah (2019)
Fabrication of zinc silicate with low cost material for optoelectronic industry has been attract interest amongst researchers. Therefore, in this research, zinc silicate glassceramic were synthesized from ZnO, B2O3 and waste rice husk as substitute for SiO2 by using conventional solid-state method. In this project, a series of zinc silicate glass with empirical formula of 55-x(ZnO)x(B2O3)45(WRHA) where x = 5, 10 and 15 wt.% fabricated as series 1. Meanwhile, 85-y(ZnO)y(WRHA)15(B2O3) where y = 25, 30, 35 and 45 wt.% fabricated as series 2. Then, the effect of controlled heat treatment from 650 °C to 800 °C on the physical, structural, morphologies, phases and optical properties were measured by using Digital Electronic Density Meter, XRD, FTIR spectroscopy, FESEM, UV-Vis and PL spectroscopy. Physical investigation using digital electronic density meter shown that the density is increased with temperature and dropped at temperature above 750 °C probably because of ZnO depletion in the sample. Structural analysis with XRD shows β-willemite phase started to occur at 700 °C and with heat treatment at 750 and 800 °C, α-willemite phase can be observed. Diffraction intensity increased with heat treatment temperature. FESEM analysis revealed that with heat treatment at 650 °C, the glassy phase improved. Heat treatment above 700 °C, it shows necking appeared and above 750 °C and at 800 °C the densification increased, the surface become smoother. FTIR spectra showed the presence of ZnO4, SiO4 and Zn2SiO4 bonds which proved the formation of zinc silicate network. The effect of heat treatment temperature showed the intensity of FTIR spectra increased which is due to the bonds become stronger. Moreover, the UV-Vis analysis to investigate willemite glass-ceramic revealed the samples’ optical band gap. The absorption edge shifted from shorter wavelength to longer wavelength with increase in temperature. Shifting process is due to formation of willemite in the sample. Meanwhile, the optical band gap showed decrement with increment of heat treatment temperature. Willemite crystal presence in the sample lead to scattering of the short wavelength light. The transition of optical band gap obtained is n = 3/2. Therefore, this ternary glass system are able to promote as a potential phosphor material for electronic devices.